Economical low-light photovoltaics by using the Pt-free dye-sensitized solar cell with graphene dot/PEDOT:PSS counter electrodes. (November 2015) - Lee, Chuan-Pei; Lin, Chin-An; Wei, Tzu-Chiao; Tsai, Meng-Lin; Meng, Ying; Li, Chun-Ting; Ho, Kuo-Chuan; Wu, Chih-I; Lau, Shu-Ping; He, Jr-Hau
Abstract: Graphene dots (GDs) are used for enhancing the performance of the poly(3, 4-ethylenedioxythiophene):polystyrenesulfonate (PEDOT:PSS)-based counter electrodes in Pt-free dye-sensitized solar cells (DSSCs). As compared to PEDOT:PSS CEs, GD–PEDOT:PSS films possess a rough surface morphology, high conductivity and electrocatalytic activity, and low charge-transfer resistance toward I − /I3 − redox reaction, pushing cell efficiency to 7.36%, which is 43% higher than that of the cell with PEDOT:PSS CEs (5.14%). Without much impact on efficiency, the DSSCs with GD–PEDOT:PSS CEs work well under low-light conditions (light intensity <13.5 mW cm −2 and angle of incidence >60°), such as indoor and low-level outdoor lighting and of the sun while the other traditional cells would fail to work. The concurrent advantage in low cost in Pt-free materials, simple fabrication processes, comparable efficiency with Pt CEs, and high performance under low-light conditions makes the DSSC with GD–PEDOT:PSS CEs suitable to harvest light for a diverse range of indoor and low-level outdoor lighting locations. Graphical abstract: Highlights: High performance solar cells under low-light illumination. Pt-free electrodes using low-cost materials and simple fabrication processes. Enhancing PEDOT:PSS electrode performance to 7.36% with graphene dots for sensitized cells. Economical energy-harvesting systems for smart-home and intelligent buildings.